Postdiverticular Stasis—Introduction of a New Etiology for Small Intestine Obstruction: A Case Series. (12th July 2012) - Mousavi, Seyed Abdollah; Karami, Hassan
Abstract : Introduction . Intestinal obstruction in the setting of Meckel's diverticulum in young age and with orange and meat bezoar is a rare, previously unreported condition. Since the obstruction point is located immediately after Meckel's diverticulum in our patients, we attempt to introduce " localized peristalsis insufficiency " as a new etiology for small intestine obstruction while reviewing the findings of previous studies. Conclusion . Intestinal obstruction in the setting of Meckel's diverticulum and with orange and meat bezoar is a rare, previously unreported condition. Considering the previous reports, we may present the theory of localized peristalsis insufficiency in patients with Meckel's diverticulum.